Deriving objective navigational measures for web usability - Rahmat, Hazwani; Zulzalil, Hazura (Praise Worthy Prize, 2013)
Navigation is one of web usability attribute besides other usability characteristic such as presentation and content. Various navigational measures (metrics) has been proposed to support web usability. However, although there are various navigational metrics available, navigation remains as root of most major web usability problems. Developers are facing difficulties in applying web usability measures due to its ambiguity thus making it prone to different interpretation among developers. While some webs are not affected by the implementation of the misinterpreted measures, some might face much worst usability condition when the misinterpreted measures are applied in the web design. This study aims to propose objective navigational measures for web usability. To ensure the measures acceptability, only dominant measures are filtered in the derivation process. The measures are then implemented in a demo web to demonstrate its applicability.